Feminist Themes in Films Directed by Men in the Chinese Movie Industry - Cheng, Linying; Li, Jing; Liu, Yunlei (Transactions on Social Science, Education and Humanities Research, 2024)
Film, as one of the mainstream media in the 21st century, has shaped societal norms, which molds public perceptions and values. With the emergence of feminism in the 21st century, it can be witnessed an increasing trend in the appearance of films on the theme of feminism. However, in the Chinese film industry, most of the positions are predominated by men (usually defined as director, producer, and writer), leaving women significantly underrepresented. This study aims to dissect the context of two films, "I am Not Madame Bovary" and "Lost in the Star", which are feminist-theme content directed by male directors. Through the detailed analysis, this study finds the underrepresentation of female voices within the film industry, along with its impact on the depiction of women and their interpersonal dynamics. This research underscores the contrast between the ostensible neutrality of film narratives and the inherent male-oriented discourse that sidelines female perspectives, which silence women's voices in the narrative fabric.